Non-destructive evaluation of bondline defect in honeycomb composite - Amjad S/O Mohamed Ali Nister (Nanyang Technological University, 2024)
With the wide range of use for honeycomb composites due to its superior strength to weight ratio and heat insulation properties, it is critical to ensure the integrity and safety of the structure is upheld. This can be carried out by Non-Destructive Testing to detect and defect present. Ultrasound testing which is widely experimented and used in various applications is able to detect defects on the subsurface levels of a structure. There are various methods that can be caried with ultrasound testing. In this project, specimens are designed with Carbon Fibre Reinforced Polymer as the face sheet with nomex honeycomb of varying dimensions as the core. The specimen is further layered to 2 layers and experiments are repeated. Between the layers of the face sheet and core, bondline defect is introduced Pulse-echo, through transmission and water immersion techniques are used to explore on identifying the defects. Despite water immersion technique was only performed up to the first layer, and testing was done only on the defect side, it displayed accurate results and C-scan imaging captured the disbond defect and it was easily comprehended. Pulse echo technique was able to detect the defect on the defect side but it was not capable of detecting the defect on the opposite side of the defect. However, this method displayed more accuracy in sizing the defect as opposed to the through transmission method. Though transmission technique displayed great capability in detecting the defect to 2 layers, however the accuracy of sizing the defect was lower as compared to pulse echo technique. It was noted the that honeycomb core size had an observable difference in the signal strength obtained while carrying out the experiments.